Traditional knowledge of wild food plants of Thai Karen and Lawa (Thailand) - Kittiyut Punchay (2020)
© 2020, Springer Nature B.V. Gathering of wild food plants represent original practices of indigenous people. The uses of wild food plant species are not only important in traditional dishes but also for the people’s health based on the medicinal properties of the plants. This study was aimed to examine the diversity patterns and similarity of wild food plants in the Karen and Lawa communities, and to identify the effects of socio-demographic factors on the traditional knowledge related to the wild food plants. The Karen and Lawa in four villages in Chiang Mai, Thailand, used 124 species of wild food plants. Most species were used as vegetables followed by species used as fruits, seasoning, and beverage. One-third of the wild food plant species had medicinal properties in addition to their uses as food. The Lawa and Karen used slightly different numbers [114 and 121, respectively] of wild food plants, but with a very large overlap of species. Socio-demographic factors such as age influenced the use patterns, whereas no significant relationship was found between gender and level of education on one side and the use of wild food plants on the other side. Knowledge of wild food plants is diverse and important in the Karen and Lawa communities which, in addition to their mostly agricultural livelihoods, maintain important elements of their original hunter-gatherer culture. We noted that the great diversity of species contributes to the dietary diversity in local communities. These findings may have implications for human food supply with potential to be substitute foods combatting food insecurity.